Comparative long-term oncological outcomes of intraoperative radiotherapy vs. whole-breast irradiation in early breast cancer: a single institute study - Chi, Mau-Shin; Ko, Hui-Ling; Yang, Tsen-Long; Liu, Ya-Fang; Chi, Kwan-Hwa; Cheng, Fiona Tsui-Fen (Frontiers in Oncology, 2024)
BackgroundIntraoperative radiation therapy (IORT) and whole breast irradiation (WBI) are both effective adjuvant radiotherapy methods for ductal carcinoma in situ (DCIS) or early-stage breast cancer (BC) patients undergoing breast-conserving surgery (BCS). We aim to evaluate the long-term oncological efficacy and refine patient selection criteria based on our findings.MethodsFemale patients who underwent either IORT or WBI from January 2016 to December 2019, with a minimum follow-up of 12 months were collected. IORT was administered as a single fraction of 20 Gray (Gy) to the lumpectomy cavity using the Axxent electronic brachytherapy system, while WBI consisted of a standard fractionation of 50 Gy in 25 fractions, along with a reduced boost of 10 Gy. The clinicopathologic characteristics and oncological outcomes were retrospectively analyzed.ResultsA total of 247 patients were enrolled, comprising 164 with BC and 83 with DCIS. Among them, 112 underwent IORT, and 135 received WBI after BCS. The median age was 62.2 years, with median tumor sizes of 1.5 cm for BC and 1.2 cm for DCIS. At a median follow-up of 64.6 months, IORT demonstrated 11 locoregional recurrences (LRR), 1 metastasis, and 1 death, compared to 4 LRR, 5 metastases, and 2 deaths in the WBI group. WBI yielded significantly higher locoregional control (97.0% vs. 90.2%, p = 0.033), although metastasis-free (96.3% vs. 99.1%, p = 0.166) and overall survival rates (98.4% vs. 99%, p = 0.688) did not differ. The LRR rate was significantly higher in the IORT group among the DCIS or BC patients (p = 0.043). The hazard ratio for locoregional recurrence significantly increased in estrogen-receptor-negative (ER-) patients in both univariate analysis (HR = 4.98, 95% CI = 1.76-14.09, p = 0.002) and multivariate analysis (HR = 40.88, 95% CI = 1.29-1297.84, p = 0.035). Additionally, IORT was associated with increased LRR in the multivariate analysis (HR = 4.71, 95% CI = 1.16-19.06, p = 0.030).ConclusionAt a long-term follow-up, the LRR rate was higher in the BCS followed by IORT, without significant differences in metastasis-free or overall survival rates. Our data confirmed the importance of exclusion ER- patients for IORT.